(untitled) (Письма в ЭЧАЯ, 2024)
We rewrite the recently constructed q-hypergeometric integral Bailey pair ina general form. Then with the help of the Bailey pair and q-beta hypergeometric sum-integral, we construct the star-triangle relation.